U.S. family cultures of sport and physical activity and 15 year olds' physical activity, sports participation, and subjective health. Issue 4 (4th July 2022) - Knoester, Chris; Allison, Rachel
ABSTRACT: Using Fragile Families and Child Wellbeing Study data ( N = 3, 011), the present study examines relationships between family cultures of sport and physical activity at age 9 and age 15, 15 year olds' physical activity, and 15 year olds' subjective health. We find moderately strong cultures of sport and physical activity; this included common support and encouragement for 15 year olds' sport and physical activity as well as 15 year olds' frequent coactivity with family and friends. Yet, gender and socioeconomic status inequalities are apparent. We also find that family cultures of sport and physical activity at age 9 appear to shape 15 year olds' cultures of sport and physical activity. Finally, indicators of stronger family cultures of sport and physical activity are positively associated with changes in 15 year olds' subjective health between the ages of 9–15 years old. Overall, our findings suggest that family cultures of sport and physical activity are integral to nurturing healthy lifestyles and that there is a need to support families and children so that sport and physical activity and positive health trajectories can be more widely experienced.